Influence of imperfections on the load capacity and stiffness of glued-in rod connections. (30th November 2019) - Ratsch, Nils; Böhm, Stefan; Voß, Morten; Kaufmann, Marvin; Vallée, Till
Highlights: With regard to the high quality standards for adhesive bonding, GiR have proven to be very robust. Only voids had a great influence on the performance; dirt, oil, and rust had little to no. The influence of the defect is relatively independent from that of the adhesive of wood. GiR in beech LVL achieve higher load capacities compared to joints made of spruce GLT. An Analysis of Variance (ANOVA) showed that the effect of most defects is not significant. Abstract: Glued-in rods (GiR), which consist of rods glued into structural elements of wood, or engineered wood products, share the manufacturing quality concerns associated to adhesively bonded joints in general. Because of the difficulties associated with the bonding process, it is often argued within the timber engineering community that under the specific conditions prevailing in construction sites, it is not possible to meet the high-quality requirements for bonded joints typically encountered in other industries. The present study presents experimental evidence gathered on 240 individual probes in which the effect of several different types of defects (excessive wood moisture content, wood chips not removed from the borehole, simulated air inclusions by mixing polystyrene spheres, oil contaminated rods, and corroded rod) was investigated with threaded rods glued into beech spruce glued laminated timber (GLT) and beech laminated veneer lumber (LVL) using four adhesives (including 2K-epoxies and a 2K-polyurethane). Results were analysed by means of an analysis of variance (ANOVA). The findings showed that glued-in rods represent a relatively robust class of adhesively bonded joints, as the majority of defects types could not be distinguished on statistical ground from the reference sets, with the notable exception of air voids leading to a significant decrease of joint capacity.